1T/2H MoSe2-on-MXene heterostructure as bifunctional electrocatalyst for efficient overall water splitting. (5th December 2019) - Li, Nan; Zhang, Yifan; Jia, Meilin; Lv, Xinding; Li, Xitao; Li, Ran; Ding, Xiaoqing; Zheng, Yan-Zhen; Tao, Xia
Abstract: Designing inexpensive yet active bifunctional electrocatalysts to directly split water is extremely desirable for the ever-broader applications of hydrogen energy. Herein, we present a cost-efficient multiphasic 1T/2H MoSe2 -on-MXene nanosheets heterostructure (denote as 1T/2H MoSe2 /MXene) as electrocatalyst for efficient overall water splitting. On one hand, the 1T/2H MoSe2 possesses abundant active sites providing relatively high electrocatalytic activity. On the other hand, the MXene nanosheets serve as high-conductive 2D substrates capable of promoting charge transfer ability and preventing 1T/2H MoSe2 from aggregation. Consequently, the 1T/2H MoSe2 /MXene catalyst in alkaline media exhibits remarkable synergy in both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) activity having advantage over pure 1T/2H MoSe2, MXene and 2H MoSe2 /MXene counterparts. To be specific, for HER performance, the 1T/2H MoSe2 /MXene reveals an overpotential (95 mV) and Tafel slope (91 mV dec −1 ); for OER performance, the 1T/2H MoSe2 /MXene shows an overpotential (340 mV) and Tafel slope (90 mV dec −1 ). Particularly, when 1T/2H MoSe2 /MXene serving as bifunctional electrocatalyst for overall water splitting, only 1.64 V is requested to attain a current density of 10 mA cm −2 . The 1T/2H MoSe2 /MXene heterostructure also exhibits good durability in overall water splitting system. Graphical abstract: Image 1 Highlights: 1T/2H MoSe2 /MXene was synthesized as bifunctional electrocatalyst for the first time. The MXene nanosheets effectively improve the conductivity and charge transfer capability of the electrode. The electrocatalytic activity of the electrode towards both OER and HER in alkaline solution is superb.